National trends in HIV pre‐exposure prophylaxis awareness, willingness and use among United States men who have sex with men recruited online, 2013 through 2017 - Sullivan, Patrick S; Sanchez, Travis H; Zlotorzynska, Maria; Chandler, Cristian J; Sineath, RC; Kahle, Erin; Tregear, Stephen (Journal of the International AIDS Society, 2020)
Introduction Pre‐exposure prophylaxis (PrEP) is a key HIV prevention technology, and is a pillar of a comprehensive HIV prevention approach for men who have sex with men (MSM). Because there have been no national data to characterize trends in the PrEP continuum in the United States, overall and for key demographic groups of MSM, we aimed to describe the extent to which PrEP awareness, willingness and use changed over time, overall and for specific groups of MSM critical for HIV prevention (e.g. Black and Hispanic MSM, younger MSM, MSM in rural areas and MSM without health coverage). Methods The American Men's Internet Survey (AMIS) is an annual survey of US MSM conducted in the United States among MSM aged ≥15 years since 2013. We analysed data on trends in elements of the PrEP continuum (awareness, willingness and use of PrEP) in a sample of 37,476 HIV‐negative/unknown status MSM from December 2013 through November 2017. We evaluated trends in continuum steps overall and among demographic subgroups using Poisson models with Generalized Estimating Equations. For 2017 data, we used logistic regression to compare the prevalence of PrEP use among demographic groups. Results Overall, 51.4% (n = 19,244) of AMIS respondents were PrEP‐eligible across study years. Between 2013 and 2017, PrEP awareness increased from 47.4% to 80.6% willingness to use PrEP increased from 43.9% to 59.5% and PrEP use in the past 12 months increased from 1.7% to 19.9%. In 2017, use of PrEP was lower for men who were younger, lived outside of urban areas, and lacked health insurance; PrEP use was not different among Black, Hispanic and white MSM. Conclusions Our data show progress in use of PrEP among US MSM, but also reveal mismatches between PrEP use and epidemic need. We call for additional support of PrEP initiation, especially among young, non‐urban and uninsured MSM. Black and Hispanic MSM report levels of PrEP use no different from white MSM, but given higher HIV incidence for Black and Hispanic MSM, parity in use is not sufficient for epidemic control or health equity.